Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1590/s1677-5538.ibju.2013.04.09
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of propiverine and terazosine combination for one year in male patients with luts and detrusor overactivity

Abstract: Purpose: To evaluate the long term efficacy and safety of the use of propiverine and terazosine combination in patients with LUTS and DO by a placebo controlled study. Materials and Methods: One hundred patients were enrolled in the study. They were randomized into two groups (each group consisted of 50 patients). Terazosine and placebo were administered to the patients in Group 1 and terazosine plus propiverine HCL was administered to Group 2. The patients were evaluated by international prostate symptom scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…The risk of publication bias estimation through funnel plots and Eger's test showed significant asymmetry. The asymmetry was particularly observed for frequency (p<0.01) with studies seeming to be missing in areas of non-significance, which could be due to reporting studies 17,18,22 required ≥3 urgency episodes per 24 h at baseline. Second, differences between alpha-blocker treatments may also be accountable for the differences in efficacy between studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The risk of publication bias estimation through funnel plots and Eger's test showed significant asymmetry. The asymmetry was particularly observed for frequency (p<0.01) with studies seeming to be missing in areas of non-significance, which could be due to reporting studies 17,18,22 required ≥3 urgency episodes per 24 h at baseline. Second, differences between alpha-blocker treatments may also be accountable for the differences in efficacy between studies.…”
Section: Discussionmentioning
confidence: 95%
“…A meta-analysis of urgency and frequency showed substantial between-study heterogeneity. The examination of individual trials and subgroup characteristics identified Lee et al 2011 22 as an outlier for both outcomes, mainly because of its wide confidence interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 10 articles with 9 RCTs were included in the analysis, with 5 RCTs [6,[8][9][10][11] for propiverine hydrochloride for overactive bladder (Figs. 2, 3, and 4) and 4 RCTs [12][13][14][15] for propiverine hydrochloride for overactive bladder and in adult with lower urinary tract symptoms (Fig. 5).…”
Section: Characteristics Of Individual Studiesmentioning
confidence: 97%
“…8 Detrusor overactivity is a urodynamic observation characterized by spontaneous or provoked involuntary detrusor contractions during the filling phase. 9 Other causes of LUTS include genitourinary cancer, urethral strictures, prostatitis, comorbid conditions, medications, and pelvic trauma or surgery. 10,11 For these reasons, management of LUTS requires a physician who is knowledgeable about the lower urinary tract.…”
mentioning
confidence: 99%